OpenMP: heterogenous execution and data movements : 11th International Workshop on OpenMP, IWOMP 2015, Aachen, Germany, October 1-2, 2015 : proceedings /: 11th International Workshop on OpenMP, IWOMP 2015, Aachen, Germany, October 1-2, 2015 : proceedings. (2015) - Unknown
No abstract available